2021
DOI: 10.1093/jamia/ocab006
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Process Modeling to Phenotype Clinician Behaviors for Exploiting the Signal Gain of Clinical Expertise (HPM-ExpertSignals): Development and evaluation of a conceptual framework

Abstract: Objective There are signals of clinicians’ expert and knowledge-driven behaviors within clinical information systems (CIS) that can be exploited to support clinical prediction. Describe development of the Healthcare Process Modeling Framework to Phenotype Clinician Behaviors for Exploiting the Signal Gain of Clinical Expertise (HPM-ExpertSignals). Materials and Methods We employed an iterative framework development approach t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 49 publications
(48 reference statements)
0
26
0
Order By: Relevance
“…Human ventilator waveform data represent several generating processes, lung physiology, ventilator mechanics, interventions, patient-ventilator interactions, and health care process model effects (Hripcsak and Albers, 2013b;Rossetti et al, 2021). In general, physiological models alone might be missing substantial contributing sources within the data.…”
Section: Introductionmentioning
confidence: 99%
“…Human ventilator waveform data represent several generating processes, lung physiology, ventilator mechanics, interventions, patient-ventilator interactions, and health care process model effects (Hripcsak and Albers, 2013b;Rossetti et al, 2021). In general, physiological models alone might be missing substantial contributing sources within the data.…”
Section: Introductionmentioning
confidence: 99%
“…Our preliminary study using the aforementioned approach has demonstrated that using nursing documentation patterns as an EWS predictor performed similarly to the Modified Early Warning Score (MEWS), one of the most widely used EWSs in clinical settings, which leverages the actual recorded values (eg, a heart rate of 60 BPM) as its predictors [ 12 ]. However, CONCERN was able to detect patient deterioration 42 hours earlier than the MEWS [ 13 ]. CONCERN’s earlier detection capabilities therefore create a more advantageous window of opportunity for clinicians to anticipate and appropriately react to impending patient deterioration.…”
Section: Introductionmentioning
confidence: 99%
“…The CONCERN CDS system will be triggered on the basis of analytics of nursing documentation through NLP, which indicates the recognition of and concerns about negative patient changes [ 13 , 15 ]. Testing of the predictive model underlying the CONCERN CDS has been conducted on retrospective data and findings have been published, including those that previously highlighted that CONCERN performs similarly to the MEWS with an improved lead time of 42 hours [ 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Standardizing and reusing such metadata definitions has two major advantages. First, it yields harmonized data sets that allow data exchange between institutions [ 3 , 4 ] and facilitate data analyses, such as multi-site phenotyping [ 5 ] or machine learning [ 6 ]. Second, medical documentation does not have to be developed from scratch reducing costs [ 7 ].…”
Section: Introductionmentioning
confidence: 99%